2020
DOI: 10.1093/jamia/ocaa137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation and diagnostic yield following evaluation of abnormal pulse detected using Apple Watch

Abstract: Objective The study sought to characterize the evaluation of patients who present following detection of an abnormal pulse using Apple Watch. Materials and Methods We conducted a retrospective review of patients evaluated for abnormal pulse detected using Apple Watch over a 4-month period. Results Among 264 included patients, clinical documentation for 41 (15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 8 publications
(10 reference statements)
0
38
0
Order By: Relevance
“…For example, although the Apple Watch has approval from the US Food and Drug Administration for their W-PPG and W-ECG technology, the device has not been adequately studied, and postmarket surveillance demonstrated a high false-positive rate, with only 15% of patients who received an abnormal pulse alert on an Apple Watch having AF confirmed. 22 Importantly, by incorporating data from the raw PPG signals and the other sensors in the watch, we were able to Values are given as % unless otherwise indicated. AF 5 atrial fibrillation; AUC area under the receiver operator characteristic curve; CI 5 confidence interval; P-ECG 5 patch electrocardiography; SENS 5 sensitivity; SENS est 5 estimated sensitivity using logistic regression; SPEC 5 specificity; SPEC est 5 estimated sensitivity using logistic regression; SR 5 sinus rhythm; TN 5 number of true-negative events (SR on P-ECG); TP 5 number of true-positive events (AF on P-ECG); W-ECG watch electrocardiography; W-PPG 5 watch photoplethysmography.…”
Section: Discussionmentioning
confidence: 99%
“…For example, although the Apple Watch has approval from the US Food and Drug Administration for their W-PPG and W-ECG technology, the device has not been adequately studied, and postmarket surveillance demonstrated a high false-positive rate, with only 15% of patients who received an abnormal pulse alert on an Apple Watch having AF confirmed. 22 Importantly, by incorporating data from the raw PPG signals and the other sensors in the watch, we were able to Values are given as % unless otherwise indicated. AF 5 atrial fibrillation; AUC area under the receiver operator characteristic curve; CI 5 confidence interval; P-ECG 5 patch electrocardiography; SENS 5 sensitivity; SENS est 5 estimated sensitivity using logistic regression; SPEC 5 specificity; SPEC est 5 estimated sensitivity using logistic regression; SR 5 sinus rhythm; TN 5 number of true-negative events (SR on P-ECG); TP 5 number of true-positive events (AF on P-ECG); W-ECG watch electrocardiography; W-PPG 5 watch photoplethysmography.…”
Section: Discussionmentioning
confidence: 99%
“…Like our results, those of prior studies raised questions about effective ways to apply wearable technology to improve health outcomes. A 2020 retrospective analysis 24 of Apple Watch alerts found that 11% of alerts were associated with a clinically actionable event. Another study of inpatients on telemetry 7 found poor sensitivity of smartwatch AF detection among patients after cardiac surgical treatment, a group known to have a high arrhythmia burden.…”
Section: Discussionmentioning
confidence: 99%
“…AI is often considered a “black-box” technology, making it difficult for some clinicians to trust the results or communicate the meaning of AI-derived findings to patients [ 135 , 136 ]. Moreover, a recent study of abnormal pulse detected by the Apple Watch found that nearly 90% of the alerts did not lead to clinically actionable diagnoses, leading to concerns of increased low-value health utilization [ 137 ].…”
Section: Artificial Intelligencementioning
confidence: 99%